Celebrity endorsers : what can´t be predicted : examining the impact of celebrity endorser news and the moderating role of event type on brand valuations and consumer’s purchase intentions - Liu, Susana Wang (2022)
As brands convert celebrity endorsements in common practice to capture consumer’s attentions and distinguish themselves amidst the advertising noise, it consequently results in these idolized individuals to yield immense power. However, in this information and media era, consumers can voice their opinions and share it in a mass scale with many others. Any news regarding celebrities are easily identified and can be widespread. So, what happens to the endorsed brand when consumers encounter positive and negative celebrity endorser news? Are endorsed brands impacted by celebrity’s news even if they are not involved in it? Furthermore, as consumers increasingly demand brands to go past profit-seeing and take a stand on sensitive topics, this study analyzes if the deeds and actions of celebrity endorsers can be transferred to the endorsed brands and if there is an event type more prone to be sensitive on consumers. Through the conduction of descriptive, exploratory and causal research, the hypotheses were raised and tested to uncover the answers raised previously. Findings negated the expected outcomes derived from positive news while identifying significant effects of celebrity transgressions in brand trust. The insights reflected a decreasing effectiveness of advertisements containing celebrity endorsers and further stated that although important, purpose and causes defended by celebrity endorsers are not equally reflected in the case of the endorsed brand.